A comparative study on lexical ambiguity that causes funniness in english and Vietnamese verbal Jokes - Ngô, Ngọc Thảo (2018)
Chuyên ngành: Tiếng Anh; Mã số: 80.22.02.01; Ý kiến về việc sao chép tài liệu: đồng ý sao chép 100%; Ý kiến về việc chuyển dạng tài liệu ( từ giấy sang điện tử): đồng ý; TM tài liệu tham khảo sau phần kết luận; Luận văn Thạc sĩ Ngôn ngữ Anh trường ĐH Thủ Dầu Một, 2018; Including 5 chapter. Chapter 1 Introduction; Chapter 2 Literature review; Chapter 3 Methodology; Chapter 4. Findings and discusson; Chapter 5. Conclusion and implications